The effects of protein phosphatase inhibitors on the duration of central sensitization of rat dorsal horn neurons following injection of capsaicin - Fang Li; Wu Jing; Zhang Xuan; Willis William D (SAGE Publishing, 2006)
Abstract Protein kinases and phosphatases catalyze opposing reactions of phosphorylation and dephosphorylation, which may modulate the function of crucial signaling proteins in central nervous system. This is an important mechanism in the regulation of intracellular signal transduction pathways in nociceptive neurons. To explore the role of protein phosphatase in central sensitization of spinal nociceptive neurons following peripheral noxious stimulation, using electrophysiological recording techniques, we investigated the role of two inhibitors of protein phosphatase type 2A (PP2A), fostriecin and okadaic acid (OA), on the responses of dorsal horn neurons to mechanical stimuli in anesthetized rats following intradermal injection of capsaicin. Central sensitization was initiated by injection of capsaicin into the plantar surface of the left paw. A microdialysis fiber was implanted in the spinal cord dorsal horn for perfusion of ACSF and inhibitors of PP2A, fostriecin and okadaic acid. We found that in ACSF pretreated animals, the responses to innocuous and noxious stimuli following capsaicin injection increased over a period of 15 min after injection and had mostly recovered by 60 min later. However, pre- or post-treatment with the phosphatase inhibitors, fostriecin or OA, significantly enhanced the effects of capsaicin injection by prolonging the responses to more than 3 hours. These results confirm that blockade of protein phosphatase activity may potentiate central sensitization of nociceptive transmission in the spinal cord following capsaicin injection and indicate that protein phosphatase type 2A may be involved in determining the duration of capsaicin-induced central sensitization.